Airline operations control - Bruce, Peter J., author. 625981; Mulholland, Chris (Writer on aviation), author. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This text is among the first to reveal the intricacies of an airline's Operations Control Centre; especially the thought processes, information flows, and strategies taken to mitigate disruptions. Airline Operations Control provides a deep level of description, explanation and detail into the activities of a range of highly professional and expert staff managing the 'sharp' end of the airline. It aims to fill a void as little is understood about this area, and very little is written for practitioners in the airline business. The book offers a comprehensive look at the make-up of the Operations Centre, its component sections, and the processes that occur both in preparing for and executing the current day's schedules. Several chapters provide real-life scenarios and demonstrate how Operations Centres manage evolving situations - what they need to take into account, and how they need to have Plan B and Plan C ready when things don't go right. This book is designed to deliver knowledge gains to both new and experienced aviation industry practitioners with regards to vital operational aspects. Additionally, it also offers students of air transport management a readily accessible and real-world-perspective guide to a crucial function present within every airline"--